Essential Components of Melanoma Histopathological Reporting: The Surgical Oncologist’s Perspective - Vinka Nurdjaja; Masato Yozu; Jon A. Mathy (Journal of Skin Cancer)
Histopathological reporting plays a critical role in guiding the surgical oncologist’s management plan in treatment of primary cutaneous melanoma. The International Collaboration on Cancer Reporting (ICCR) espouses various components of structured histopathological reporting as “essential” or “recommended.” From a surgical oncologist’s perspective, we discuss the clinical relevance of each essential component, as well as prognostic and treatment implications with regard to treatment planning.